Hear the Machine, Fear the Machine: George Antheil’s Ballet Mécanique and Listener Ambivalence in the Twentieth Century - Sumner, Carolyne (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2019)
George Antheil’s Ballet Mécanique is notorious for its cacophonous sonorities, its industrial allusions, and its use of mechanical instruments, notably the player piano. Despite a successful première in Paris in 1926, the 1927 American reception of the piece was viscerally critical. Drawing upon contemporary documents, this article reconsiders the American reception of the ballet in light of the relationship between early twentieth-century American audiences and the mechanical. It suggests that through its use of mechanized instruments, specifically the player piano, Ballet Mécanique exacerbated anxiety and skepticism about the mechanical and mirrored a growing fear about the destructive consequences of a mechanized society.